2010
DOI: 10.3391/ai.2010.5.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the non-native fish Salminus brasiliensis (Cuvier, 1816), in a global biodiversity ecoregion, Iguaçu River, Paraná River basin, Brazil

Abstract: This technical paper presents results from pilot field trials conducted on the novel use of a biodegradable jute material to eradicate the highly invasive aquatic macrophyte Lagarosiphon major Ridley from Lough Corrib, Ireland. The results demonstrate the ability of the jute material to comprehensively kill L. major and to restore native macrophyte communities to areas of the lake that were previously overgrown with this priority invasive species. To date, eight indigenous plant species (four charophytes and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…Broader studies have already indicated that larger carnivores consume a wide array of small species and juveniles (Juanes et al, 2002;Bozza, Hahn, 2010;Santos et al, 2012), while B. orbignyanus has low potential as a consumer of Nile Tilapia (Santos et al, 2009). Furthermore, P. corruscans shows ambushing behavior in shallow areas with different densities of macrophytes (Sabino, Zuanon, 1998;Giaquinto, Hoffmann, 2010;Petry et al, 2010) and S. brasiliensis has high potential for predation and also good maneuvering and swimming abilities (Agostinho et al, 2007;Gubiani et al, 2010;Santos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broader studies have already indicated that larger carnivores consume a wide array of small species and juveniles (Juanes et al, 2002;Bozza, Hahn, 2010;Santos et al, 2012), while B. orbignyanus has low potential as a consumer of Nile Tilapia (Santos et al, 2009). Furthermore, P. corruscans shows ambushing behavior in shallow areas with different densities of macrophytes (Sabino, Zuanon, 1998;Giaquinto, Hoffmann, 2010;Petry et al, 2010) and S. brasiliensis has high potential for predation and also good maneuvering and swimming abilities (Agostinho et al, 2007;Gubiani et al, 2010;Santos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to notice, however, that the tanks could have limited the space for swimming and, in a larger setting, Salminus brasiliensis and Brycon orbignyanus might be more defensive, as here they may be unable to swim to the middle layer and the surface, which would be their typical behavior in their natural habitats. Nevertheless, S. brasiliensis is an aggressive predator that can easily adapt to changes in environmental conditions (Gubiani et al, 2010). Most of the preys are also at the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Esse isolamento das espécies fez com que cerca de 70% das espécies de peixes nativos do rio Iguaçu não possa ser encontrada em nenhuma outra área do planeta (Baumgartner et al, 2012). Recentemente, a espécie Salminus brasiliensis, popularmente conhecida como "dourado", foi introduzida no rio Iguaçu (Gubiani et al, 2010;Ribeiro et al, 2017). O dourado é um predador visual eficiente, se alimenta de uma grande variedade de presas e é extremamente apreciado na pesca (Vitule et al, 2014), potencial motivo pelo qual a espécie foi introduzida nesse rio.…”
Section: Invasão De Espécies Exóticasunclassified
“…In terms of conservation, the drainage is of special concern because it contains a high proportion of endemic fish species (Abell et al., ), many of which are endangered (Rosa and Lima, ). The unique fish fauna of the drainage is threatened due to a variety of factors, including habitat degradation by human activities, water pollution, impoundments, fisheries, and the introduction of alien fishes (Myers, ; Gubiani et al., ).…”
Section: Introductionmentioning
confidence: 99%